2010
DOI: 10.1111/j.1365-2672.2010.04715.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of typical and atypical virulence genes in vibrio isolates belonging to the Harveyi clade

Abstract: Aims: The study was aimed at investigating the presence of typical and atypical virulence genes in isolates belonging to the Harveyi clade (Vibrio harveyi and Vibrio campbellii). Methods and Results: Forty-eight vibrio isolates belonging to the Harveyi clade were screened for the presence of virulence genes that are typical for these bacteria and those found in human pathogenic vibrios such as Vibrio cholerae, Vibrio parahaemolyticus and Vibrio vulnificus and aquatic pathogenic Vibrio anguillarum. The virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 64 publications
3
49
1
Order By: Relevance
“…It was proposed that such pathogeninduced blooms drive conjugative horizontal gene transfer between different Enterobacteriaceae and are responsible for the evolution of both pathogens and commensals. Thus, the human intestinal tract may represent an ecological niche that stimulates the occurrence of horizontal gene transfer both among different strains of V. parahaemolyticus and between V. parahaemolyticus and other commensal species (65)(66)(67)(68). What remains unknown is the frequency of such evolutionary events, although it is likely to be relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that such pathogeninduced blooms drive conjugative horizontal gene transfer between different Enterobacteriaceae and are responsible for the evolution of both pathogens and commensals. Thus, the human intestinal tract may represent an ecological niche that stimulates the occurrence of horizontal gene transfer both among different strains of V. parahaemolyticus and between V. parahaemolyticus and other commensal species (65)(66)(67)(68). What remains unknown is the frequency of such evolutionary events, although it is likely to be relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the genomes of several species of Vibrio whose genomes have been completely sequenced encode homologues of HlyA in chromosome II, with identity values at the amino acid level ranging from 47% to 50%. These Vibrio species include V. cholerae (23), V. anguillarum (24), V. fluvialis (25), V. furnissii (26), and V. harveyi (27), among others.…”
Section: Resultsmentioning
confidence: 99%
“…1990). Importantly, pathogenicity appears not to be species dependent, but rather a strain characteristic as some strains belonging to one specific species can be highly pathogenic, whereas other strains are avirulent (Austin & Zhang 2006; Ruwandeepika et al. 2010).…”
Section: Impact Of Vibriosis Caused By Harveyi Clade Vibrios On the Amentioning
confidence: 99%